2018
DOI: 10.1111/cobi.13035
|View full text |Cite
|
Sign up to set email alerts
|

Ecological consequences of forest elephant declines for Afrotropical forests

Abstract: Poaching is rapidly extirpating African forest elephants (Loxodonta cyclotis) from most of their historical range, leaving vast areas of elephant-free tropical forest. Elephants are ecological engineers that create and maintain forest habitat; thus, their loss will have large consequences for the composition and structure of Afrotropical forests. Through a comprehensive literature review, we evaluated the roles of forest elephants in seed dispersal, nutrient recycling, and herbivory and physical damage to pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
70
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 73 publications
(158 reference statements)
1
70
0
Order By: Relevance
“…Mammals are key ecosystem engineers, frequent apex predators, and providers of important ecosystem services e.g., 31,32 . Future dynamics of mammal populations can therefore determine overall ecosystem change 33 .…”
mentioning
confidence: 99%
“…Mammals are key ecosystem engineers, frequent apex predators, and providers of important ecosystem services e.g., 31,32 . Future dynamics of mammal populations can therefore determine overall ecosystem change 33 .…”
mentioning
confidence: 99%
“…Despite our low sample size, the present study produced some interesting results. Previous studies found that unprotected roads have a barrier effect in elephant displacements, but not in the case of roads located inside protected areas (Blake et al, ; Kolowski et al, ; Poulsen et al, ; Schuttler et al, ). Given that our road is a protected road inside a National Park, our results are consistent with these previous studies.…”
Section: Discussionmentioning
confidence: 94%
“…Forest elephant ( Loxodonta cyclotis Matschie, 1900) movement and feeding behaviour (pollarding, peeling and trampling) modify forest structure, controlling the availability of resources for other organisms (Poulsen et al, ) and maintaining habitats with open canopy such as bais—forest clearings—(Fishlock, ; Metsio Sienne, Buchwald, & Wittemyer, ; Turkalo, ). A reduction in the abundance of forest elephants can alter plant communities and ecosystem function (Poulsen et al, ), which may have implications for the entire ecosystem due to cascading effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maisels et al (2013) showed that the forest elephant declined by 62% in Central Africa between 2002 and 2011 and now occupies less than 25% of its potential range. This decline is concerning, as elephants are not only conservation flagships but also keystone species and ecosystem engineers (Buechner & Dawkins, 1961;Laws, Parker, & Johnson, 1975;Poulsen et al, 2017).…”
Section: Introductionmentioning
confidence: 99%